Prognostic value of maximum standard uptake value, metabolic tumor volume, and total lesion glycolysis of positron emission tomography/computed tomography in patients with nasopharyngeal carcinoma: A systematic review and meta-analysis. Issue 37 (September 2017) - Li, Qingfang; Zhang, Jing; Cheng, Wei; Zhu, Chenjing; Chen, Linyan; Xia, Fan; Wang, Manni; Yang, Fuyao; Ma, Xuelei
Abstract: Background: The maximal standard uptake value (SUVmax), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) of positron emission tomography/computed tomography (PET/CT) in patients with nasopharyngeal carcinoma (NPC) perform as new prognostic factors, but the outcomes of the published articles were inconclusive. In this meta-analysis, we evaluated the prognostic value of SUVmax, MTV, and TLG of PET/CT in patients with NPC. Methods: Relevant English articles were searched in PubMed and EMBASE. The data of patients and the survival outcomes were extracted. Pooled hazard ratios (HRs) were accounted to assess the prognostic value of the SUVmax, MTV, and TLG. Results: This meta-analysis combined 10 primary studies including 941 patients with NPC. The combined HRs (95% confidence interval [CI] of higher SUVmax, higher MTV, and higher TLG for event-free survival were 2.33 (95% CI, 1.39–3.91, P = .001), 2.51 (95% CI, 1.61–3.91, P < .0001), and 2.74 (95% CI, 1.91–3.93, P < .00001), respectively. Regarding overall survival, the combined HRs were 2.50 (95%CI, 1.65–3.78, P < .0001) with higher SUVmax, 3.30 (95% CI, 1.92–5.69, P < .0001) with higher MTV and 3.18 (95% CI, 1.70–5.96, P = .0003) with higher TLG. Conclusion: SUVmax, MTV, and TLG were significant prognostic predictors in patients with NPC. And the results suggested that higher SUVmax, MTV, and TLG were associated with worse prognosis.